Nitrogen top dressing just before irrigation improves wheat growth, productivity, nitrogen use efficiency and profitability - Gill, Subhash Chander; Sharma, Ramesh Kumar; Tripathi, Subhash Chandra; Chhokar, Rajender Singh; Meena, Raj Pal; Jha, Ankita (Journal of Cereal Research, 2019)
A four year field study was conducted from 2010-11 to 2013-14 at the research farm of ICAR-Indian Institute of Wheat and Barley Research, Karnal, Haryana to evaluate the influence of timing and frequency of urea top dressing on wheat productivity. The 13 treatments consisted of three nitrogen levels (90, 120 and 150 kg N ha-1), two time of application (just before applying irrigations and about a week after irrigations when it was possible to walk in the field) and two schedule of application (three equal splits as 1/3rd basal, 1/3rd at first irrigation and 1/3rd at second irrigation;and four equal splits as 1/4th basal, 1/4th at first irrigation, 1/4th at second irrigation and1/4th at third irrigation) along with one absolute control. The study revealed that urea top dressed just before irrigation and nitrogen splitted in three equal doses led to better crop growth, yield attributes and yield of wheat leading to improved agronomic NUE (22.5-29.8 kg grain kg-1 applied N) than urea top dressed after irrigation and nitrogen splitting in four equal doses at all levels of nitrogen application (90-150 Kg ha-1). The highest wheat productivity was recorded with 150 kg N ha-1 applied in three splits with top dressing just before irrigation. Additional yield of 2.70-5.21q ha-1 (average 3.94 q ha-1) was produced when urea was applied just before irrigation as compared to ureatop dressed after irrigatin. This yield gain was 5.93 to 10.83 percent (average 8.36 %). This practice gave additional benefit of Rs. 4680 to 9043 ha-1 (average Rs. 6843 ha-1).Â Doi.org/10.25174/2249-4065/2019/83006